The rise of biofuels in IR: the case of Brazilian foreign policy towards the EU - Lorenzo, Cristian A. (2016)
Biofuels are a growing alternative energy source. In a context of their growing global consumption, Brazil has shown particular interest in the European market. This paper analyses Brazilian foreign policy on biofuels towards the EU during Lula da Silva’s administration (2003–10). It examines the emergence of biofuels at a global level, the main guidelines of Brazilian foreign policy, Brazilian environmental foreign policy and, finally, the Brazilian political response to changes in European law.